1998
DOI: 10.1111/j.1469-7793.1998.215by.x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the [1,2‐13C]acetate recovery factor for correction of [U‐13C]palmitate oxidation rates in humans

Abstract: The validity of estimations of plasma fatty acid oxidation using tracers has often been questioned. The appearance of isotopic markers in breath CO2 is delayed and incomplete. Recently suggestions have been made that substantial amounts of tracer are incorporated into products of the tricarboxylic acid cycle (e.g. glucose, glutamine and glutamate) and that an acetate correction factor can be used to correct for tracer fixation. In the present study we investigated whether the appearance of 13CO2 during a separ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
93
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(98 citation statements)
references
References 16 publications
4
93
1
Order By: Relevance
“…where TTRCO 2 is the breath 13 C/ 12 C ratio at a given time point, VCO 2 is carbon dioxide production (l/min), k is the volume of 1 mole of CO 2 (22.4 l/mol), and Ar is the fractional 13 C label recovery in breath CO 2 observed after the infusion of labelled acetate [27,31,32], calculated as:…”
Section: Methodsmentioning
confidence: 99%
“…where TTRCO 2 is the breath 13 C/ 12 C ratio at a given time point, VCO 2 is carbon dioxide production (l/min), k is the volume of 1 mole of CO 2 (22.4 l/mol), and Ar is the fractional 13 C label recovery in breath CO 2 observed after the infusion of labelled acetate [27,31,32], calculated as:…”
Section: Methodsmentioning
confidence: 99%
“…Indeed, labeled carbons were found in glutamate and glutamine and in lower quantity in glucose and lactate and pyruvate (15). On the basis of the observation that acetate is converted into acetyl-CoA and directly enters the TCA cycle, Sidossis et al (14) were the first to propose that infused [ 14 C]acetate can be used to correct for the retention of a 13 C-fatty acid ( 13 C-FA) in the organism.…”
mentioning
confidence: 99%
“…Together with the low intraindividual coefficient of variation (CV; 4%), this suggested that although the iARF is reproducible it should be measured in every subject, except when only the group mean data are of interest. In many countries the use of radioactive isotopes is restricted for ethical reasons, and the conclusions of Schrauwen and colleagues (12,13) imply that two separate tests, performed under identical conditions, are needed to determine the iARF required to correct the tracer oxidation data. Although this might be feasible for infusion studies given the relatively short duration required to obtain a steady state (Ϸ2 h) (13), it presents operational constraints for studies investigating dietary fat oxidation that require Ն10-h tests due to digestion and trafficking processes.…”
mentioning
confidence: 99%
See 2 more Smart Citations